2020
DOI: 10.1016/j.tree.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Hygric Niches for Tropical Endotherms

Abstract: Biotic selective pressures dominate explanations for the evolutionary ecology of tropical endotherms. Yet, abiotic factors, principally precipitation regimes, shape biogeographical and phenological patterns in tropical regions. Despite its importance, we lack a framework for understanding when, why, and how rain affects endotherms. Here, we review how tropical birds and mammals respond to rain at individual, population, and community levels, and propose a conceptual framework to interpret divergent responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 129 publications
(139 reference statements)
8
52
0
1
Order By: Relevance
“…In mechanistic species distribution models, however, the ecological niche of a species is not inferred from its realized niche but derived from a calculation of the fundamental niche of the organism, defined as the full range of conditions and resources suitable for survival and reproduction (Kearney & Porter, 2009). In the last decade, mechanistic models have become central to uncovering the potential effects of global climatic change on species viability and distribution (Boyle et al, 2020; Sinervo et al, 2010). Since properties of the fundamental niche are determined by organismal traits, current research aims to better understand how morphological, physiological and behavioural properties of organisms constrain their fundamental niche and ultimately define their ecological niche and distribution.…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In mechanistic species distribution models, however, the ecological niche of a species is not inferred from its realized niche but derived from a calculation of the fundamental niche of the organism, defined as the full range of conditions and resources suitable for survival and reproduction (Kearney & Porter, 2009). In the last decade, mechanistic models have become central to uncovering the potential effects of global climatic change on species viability and distribution (Boyle et al, 2020; Sinervo et al, 2010). Since properties of the fundamental niche are determined by organismal traits, current research aims to better understand how morphological, physiological and behavioural properties of organisms constrain their fundamental niche and ultimately define their ecological niche and distribution.…”
Section: Background and Summarymentioning
confidence: 99%
“…Total evaporative loss (TEWL) comprises both the water lost through the skin epidermis or exoskeleton (cutaneous water loss, CWL) and via the respiratory system (respiratory water loss, RWL). Although functional traits such as desiccation resistance and behavioural traits are also important for hydroregulation, the standard rate of EWL has proven to be a relevant metric to assess water regulation strategies, and to scale the susceptibility of organisms to drought, habitat aridity or salinity in birds (Albright et al, 2017; Boyle et al, 2020), mammals (Van Sant et al, 2012), non‐avian reptiles (Brischoux et al, 2012; Cox & Cox, 2015), amphibians (Lertzman‐Lepofsky et al, 2020) and insects (Addo‐Bediako et al, 2001). However, to our knowledge, there has been no attempt to compile and annotate a global database of all published EWL records in terrestrial animals, including those of squamate reptiles.…”
Section: Background and Summarymentioning
confidence: 99%
“…Tropical forest ecosystems rest on complex webs of interspecific interactions and are acutely attuned to variation in the phenology and volume of annual rainfall (Leigh et al 1985, Levi et al 2019, Boyle et al 2020). In this 12‐year study of an insectivorous forest bird in central Panama, we found that many adults failed to breed in El Niño‐like years, which were associated with abnormally long dry seasons and frequent high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…El Niño phases, which in the northern Neotropics are associated with sunny conditions and drought, are predicted to increase in both frequency and severity as the climate warms (Yeh et al 2009, Cai et al 2014). Projected consequences in this region include extended dry seasons; more frequent droughts, floods and fires; and increased unpredictability in the amount and timing of seasonal rainfall (Fu et al 2013, Chadwick et al 2016), with potentially drastic effects on the behavior, distribution and viability of tropical species (Wright et al 1999, Şekercioğlu et al 2012, Lenoir and Svenning 2015; reviewed by Boyle et al 2020). In a 33‐year demographic study of Panamanian forest birds, Brawn et al (2017) found that population growth rates of many species declined following years with longer dry seasons, associated with El Niño events.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, researchers have shown an increased interest in untangling questions of ecological niche related to species distribution. Such as whether niche is conservatism in varied situation and scale (Peterson et al., 2011; Wiens & Graham, 2005), what is the relationship between niche breadth and range at latitudinal gradients (Boyle et al., 2020; Lancaster, 2016; Saupe et al., 2019; Sunday et al., 2011), how will organisms response to a novel environment (Davidson et al., 2011; Polechová et al., 2009; Spence & Tingley, 2020; Sutter & Kawecki, 2009; Szűcs et al., 2017). These critical scientific questions often derive from a story of organisms succeed or fail to establish when they arrived at a new area beyond their native range, because such alien species may pose challenges to the integrity of local ecosystems and biodiversity conservation (Tingley et al., 2014; Vilà et al., 2010).…”
Section: Introductionmentioning
confidence: 99%